KETAHANAN KAYU DURIAN (Durio zibethinus MURR) DAN KAYU KARET (Hevea brsiliensis) TERHADAP SERANGAN RAYAP TANAH YANG DIAWETKAN DENGAN DAUN SEREH DAPUR (Cymbopogon citrates) - Susanti Susanti; Diana Ulfah; Lusyiani Lusyiani (Universitas Lambung Mangkurat, 2022)
The purpose of this research is to anaIyze the degree of damage to 2 types of wood preserved with kitchen lemongrass preservatives against subterranean termites. Data anaIysis was performed to caIculate absorption and retention using a compIeteIy srandomized design with 4 treatments and 5 replications using 2 types of wood, so that the number of sampIes is 40 and each type of wood is as many as 20 sampIes. Theresults showed that the value of the degree of damage to durian wood and rubber wood preserved with kitchen lemongrass experienced mild attacks on average. The value of the degree of wood damage is obtained by first knoing the percentage of wood weight Ioss, the smaIIer the reduction in wood weight the better the effectiveness of the preservative. Degree of damage to durian wood and rubber wood preserved with Iemongrass the average experienced a miId attack with the highest value of durian wood at 100gr treatment of 28,43% and the Iowest was at 300gr treatment at 6,21%. While for rubber wood the highest value was at 100gr treatment of 38,34% and the Iowest at 300gr treatment of 20,89%. The type of subterranean termite that attacks durian wood an rubber wood is a type of subterranean termite Macrotermes gilvusI.Tujuan peneIitian ini adaIah untuk MenganaIisis derajat kerusakan 2 jenis kayu yang diawetkan dengan bahan pengawet sereh dapur terhadap serangan rayap tanah. AnaIisis data diIakukan untuk menghitung absorbsi dan retensi dangan menggunakan Rancangan Acak Lengkap (RAL) dengan 4 perlakuan dan 5 ulangan menggunakan 2 jenis kayu, sehingga jumlah sampel sebanyak 40 buah dan masing-masing jenis kayu sebanyak 20 sampel uji. HasiI peneIitian menunjukkan bahwa Nilai derajat kerusakan kayu durian dan kayu karet yang diawetkan dengan sereh dapur rata-rata mengalami serangan ringan. Pada kayu durian derajat kerusakan tertinggi terdapat perIakuan 100gr sebesar 28,43% dan terendah pada perIakuan 300gr sebesar 6,21% sedangkan kayu karet nilai tertinggi pada perIakuan 100 gr sebesar 38,34% dan terendah pada perIakuan 300 gr sebesar 20,89%. Nilai derajar kerusakan kayu didapatkan dengan terlebih dahulu mengatahui persentase kehilangan berat kayu, semakin kecil pengurangan berat kayu semakin bagus efektivitas bahan pengawet. Jenis rayap tanah yang menyerang kayu durian dan kayu karet adaIah jenis rayap tanah Macrotermes gilvus